The Rise of Web 2.0 and Digital Narcissism: Rethinking the Aesthetics of Death - Thapa, Prakash (The Outlook: Journal of English Studies, 2023)
The study aims to analyze the posts related to death on social media platforms like Facebook and Twitter. Thus, the study examines the gravity of death among the social media users and the impact of digital narcissism on the aesthetics of death. The theoretical framework for this study is based on Christopher Lasch's book The Culture of Narcissism, which provides insights into the influence of web 2.0, particularly the digital platforms that are used to post death related contents. The study utilizes a summative content analysis approach, focusing on selected statuses and corresponding comments on Facebook and Twitter that pertain to death. The findings of the summative content analysis suggest that Facebook and Twitter have been poorly managed, leading to mistreatment of human values and attitudes towards death. For instance, insensitive comments on the death-related posts indicate a form of abuse within these digital platforms. Additionally, the study highlights the growing use of emojis in expressing grief and mourning on the Web 2.0 platforms. The study concludes that the rise of Web 2.0 such as social media platforms has led to a shallow and often disrespectful portrayal of death, ultimately diminishing its intrinsic beauty and significance.